Formation of rigid, non-flight forewings (elytra) of a beetle requires two major cuticular proteins - Arakane, Yasuyuki; Lomakin, Joseph; Gehrke, Stevin H.; Hiromasa, Yasuaki; Tomich, John M.; Muthukrishnan, Subbaratnam; Beeman, Richard W.; Kramer, Karl J.; Kanost, Michael R. (My University, 2012)
Insect cuticle is composed primarily of chitin and structural proteins. To study the function of structural cuticular proteins, we focused on the proteins present in elytra (modified forewings that become highly sclerotized and pigmented covers for the hindwings) of the red flour beetle, Tribolium castaneum. We identified two highly abundant proteins, TcCPR27 (10 kDa) and TcCPR18 (20 kDa), which are also present in pronotum and ventral abdominal cuticles. Both are members of the Rebers and Riddiford family of cuticular proteins and contain RR2 motifs. Transcripts for both genes dramatically increase in abundance at the pharate adult stage and then decline quickly thereafter. Injection of specific double-stranded RNAs for each gene into penultimate or last instar larvae had no effect on larval–larval, larval–pupal, or pupal–adult molting. The elytra of the resulting adults, however, were shorter, wrinkled, warped, fenestrated, and less rigid than those from control insects. TcCPR27-deficient insects could not fold their hindwings properly and died prematurely approximately one week after eclosion, probably because of dehydration. TcCPR18-deficient insects exhibited a similar but less dramatic phenotype. Immunolocalization studies confirmed the presence of TcCPR27 in the elytral cuticle. These results demonstrate that TcCPR27 and TcCPR18 are major structural proteins in the rigid elytral, dorsal thoracic, and ventral abdominal cuticles of the red flour beetle, and that both proteins are required for morphogenesis of the beetle's elytra.
Citation: Arakane Y, Lomakin J, Gehrke SH, Hiromasa Y, Tomich JM, Muthukrishnan S, et al. (2012) Formation of Rigid, Non-Flight Forewings (Elytra) of a Beetle Requires Two Major Cuticular Proteins. PLoS Genet 8(4): e1002682. https://doi.org/10.1371/journal.pgen.1002682
Keywords: Elytra; Beetle; Cuticular proteins; Red flour beetle; Forwings